Interface critique at large - Dieter, Michael (Convergence (London, England), 2024)
This article considers how the pursuit of problematization advocated by Agre’s concept of critical technical practice has been articulated in relation to the increasing proliferation of interfaces across everyday life. While the ethos of Agre’s work to bridge the split identity of critique and craft can readily be found in reflexive design or software art, these cases are not always situated within broader ecologies of practice that also grapple with the asymmetries and exploitative aspects of interface design. Drawing from software studies and media theoretical accounts of the interface as a fluid milieu, I provide a navigational matrix to contextualize modes of interface critique at large, namely specifying traps and enclosures, surfacing asymmetries and augmenting alternatives. I argue, finally, that these modes provide an invitation to develop new metacritical theories and common capacities, particularly through the possibilities of grappling with systems of domination otherwise built to prefigure our experiences of them.